Best Answer

x raised to the power 36 is x36. Without a value for x, there is nothing to solve!

Q: How do you solve x raised to the power of 36?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6 raised to the second power is equal to 36.

(x-3)3 = (x-3)*(x-3)*(x-3) =(x-3)*(x2-6x+9) = x3 - 9x2 + 27x - 27

x=18

x to the power of 1 means x

If: x4 = 36 Then: x = 2.4494897428

Related questions

6 raised to the second power is equal to 36.

62 = 6 x 6 = 36

the question is to solve (x^2-5x+5)^(x^2-36)=1

(x-3)3 = (x-3)*(x-3)*(x-3) =(x-3)*(x2-6x+9) = x3 - 9x2 + 27x - 27

(√x)^36 = √(x^36) = x^18.

x=18

x to the power of 1 means x

Reflexivity is a property of equality, i.e., X = X is always true. Thus -7 raised to the power of 3 equals -7 raised to the power of 3 is true.

It is always negative when raised to an odd power and always positive when raised to an even power -2 to the third power = -2 x -2 x -2 = -8 -2 to the fourth power = -2 x -2 x -2 x -2 = +16

If: x4 = 36 Then: x = 2.4494897428

x2-13x+36=(x-9)(x-4)=0 x=9 or x=4

36